A lineage without primogeniture? The inheritance transmission strategy of the Hurtado de Mendoza family during the Late Middle Ages (Edad Media. Revista de Historia, 2025)
The present article examines the study of patrimonial transmission conducted by the Hurtado de Mendoza lineage from the late 14th century to the early 16th century. The primary focus will be on their lordships in Álava, where the lineage had its ancestral lands. Additionally, the article will address the question of whether they truly established a primogeniture (mayorazgo) that connected their heritage, and the consequences this had for the lineage's development, culminating in their elevation to the title of Counts of Orgaz in the mid-16th century.
Keywords: Lineage; Heritage; Primogeniture; Álava; Castile